(untitled) (Linguostylistic Studies, 2020)
The nicknames, which come into being as supplementing the person’s official name, are informal anthroponyms by which the environment individualizes or characterizes a person. Marking people with nicknames is a characteristic feature of the football discourse in the whole world. In Ukrainian linguistics, informal person’s names of football players have not been the object of study yet, that is why their analysis is still topical. The aim of the article is to analyze informal names of football players who played in the Ukrainian teams in the 20-80s of the ХХth century. It enables scholars to trace the tendencies in creating informal personal names and also can contribute to drawing social-linguistic conclusions about anthroponym usage in sports discourse.The basic method of the study is discursive analysis of the facts taken from printed sources (first of all from the Ukrainian sports media of that time) and their interpretation. Among diverse ways of creating football players’ nicknames in the Soviet period, the most effective were various transformations of players’ surnames, most often by truncating last names. A lot of nicknames were created by cutting football players’ first names or surnames and also by adding to them suffixes with diminutive semantics. Many informal names are the diminutive forms of the players’ names. Among this type of nicknames, there are those created according to the Ukrainian patterns and also in accordance with the Polish, Hungarian, and Russian patterns of creating diminutive forms of names. During that period, the patronymic names were used as nicknames for the first time. There were a lot of informal names which were created metaphorically on the basis of people’s appearance or character features, or both at the same time. Analysis of the Ukrainian football players’ nicknames in 20-80s shows that the motivational basis for those anthroponyms creation is the player’s surname, its diminutive form, and features. The ways of creating those names involve metaphors and parts of surnames. The prospects of the studies are tracing dynamics of creating football players’ nicknames in various periods of the Ukrainian football development.